Decision-Making System for KIP IAIN Bukittinggi Scholarship Recipients Using the SAW and TOPSIS Methods - Uqwatul Alma Wizsa; Yulifda Elin Yuspita; Wikasanti Dwi Rahayu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The KIP scholarship is one of the scholarships available at IAIN Bukittinggi, and prospective recipients will be chosen based on the number of quotas available. Thus far, the selection process has been carried out by calculating the total value based on the sum of the percentages of each criterion arranged according to the level of importance. The procedure does not include a decision-making system for determining whether or not to accept the KIP scholarship. As a result, a decision support system is required to quickly and accurately determine which students are eligible for scholarships. In this research, the decision-making system compares the SAW and TOPSIS methods, with the latter using normalized weights in calculating the preference value as a determining value for alternative scholarship recipients to be selected. The SAW method was found to be more sensitive than the TOPSIS method in the data for the KIP scholarship 2020 recipients at IAIN Bukittinggi, with a sensitivity value of 96.87 compared to 81.96 for the TOPSIS method. Based on these findings, the SAW method can be recommended as a decision return system for KIP scholarship recipients to study at IAIN Bukittinggi the following year.